Enabling Biodiversity-Informed Architecture Through Ontology-Driven Data Integration - Albin Ahmeti; Defne Sunguroglu Hensel; Cédric Pruski; Jakub Tyc; Michael Hensel (Applied Sciences)
Urban biodiversity is essential for sustainable cities, as it helps address the challenges of environmental degradation, ecosystem loss, species decline, and increased vulnerability to climate hazards, which negatively affect human health and well-being. ECOLOPES (ECOlogical building enveloPES) aims to develop a design approach for multi-species as stakeholders to achieve regenerative urban ecosystems. Integrating the diverse data required for stakeholders and beyond—spanning the life sciences, geography, and architecture—and utilising it for design presents a significant challenge. This paper introduces an ontology-driven approach that utilises ontology-based data management (OBDM) as a framework for integrating diverse data sources, enabling ecologists and architects to design sites and buildings that foster urban biodiversity. OBDM offers a unified view of multiple data sources through an ontology, enabling query and update operations to be performed directly on the integrated data. The proposed ontology, developed in collaboration with domain experts and adhering to Semantic Web and Linked Data best practices, serves as a mediator between life sciences data (e.g., species distribution and habitats) and geometric information (e.g., maps and voxel models of building structures). This integration enables the adaptation of sites, buildings, and geometries, respectively, to create habitats that attract and support urban wildlife, contributing to ecological sustainability. The paper illustrates the practical utility of the ontology through a case study, highlighting its role in guiding building designs that promote species attractiveness and urban biodiversity.